INTEGRATION OF HOLISTIC APPROACHES IN CHRONIC DISEASE MANAGEMENT: A CASE STUDY ON IMPROVING THE QUALITY OF LIFE FOR DIABETES MELLITUSPATIENTS THROUGH INTERDISCIPLINARY APPROACHES, PATIENT EMPOWERMENT, AND UTILIZATION OF CUTTING-EDGE HEALTH TECHNOLOGIES - Doby Indrawan; H. MR. Ulung Sembiring; Emdat Suprayitno; Eka Budi Yulianti; Mohamad Khairi Bin Haji Othman (Adisam Publisher, 2024)
This comprehensive research investigates the integration of holistic approaches in managing chronic diseases, focusing on enhancing the quality of life for individuals diagnosed with Diabetes Mellitus. Employing a robust case study methodology, the study meticulously examines the intricate interplay of interdisciplinary approaches, patient empowerment strategies, and incorporating state-of-the-art health technologies within diabetes care. The primary objective is to unravel the synergistic effects of these multifaceted interventions and assess their collective impact on patient outcomes. This research contributes to the growing body of knowledge on innovative healthcare models by offering insights into the efficacy of a patient-centric framework for chronic disease management. Through a nuanced exploration of the convergence of diverse interventions, this study seeks to provide actionable findings that resonate with healthcare professionals, policymakers, and researchers. The goal is to inform and guide future strategies for chronic disease management, particularly in Diabetes Mellitus, to elevate the quality of care and patients' overall well-being. This research promises to fill a critical gap in current literature and serve as a foundational resource for those dedicated to advancing healthcare practices through holistic and patient-focused approaches.